Implementation of Management Practices in MSMEs’ Village for Business Performance and Sustainability Improvement: A Case Study in Bantargadung Village, Bantargadung Sub-Dicstric, Sukabumi Regency, West Java. - Gursida, Hari; Herdiyana Herdiyana; Muharam, Hari; Pranowo, Agus Setyo; Hanan, Sufrin; Hadiyat, Yayan (Institut Teknologi dan Bisnis Semarang, 2025)
Management practices in Micro, Small, and Medium Enterprises (MSMEs) in rural areas play a crucial role in enhancing business sustainability and competitiveness. This article explores various management strategies that rural MSMEs can implement to optimize their business operations. Through training and mentoring programs, MSME actors are provided with knowledge and skills in financial management, marketing, and operational management. Community service activities (PkM), conducted in conjunction with research activities using a case study approach on MSMEs in Bantargadung Village, Bantargadung Subdistrict, Sukabumi Regency, have formulated a management practice model for the sustainability of rural MSMEs. This model can be further developed to advance rural MSMEs, aiming to improve the village economy, enhance rural independence, stimulate economic growth, create jobs, and reduce unemployment rates in rural areas, ultimately improving the welfare of rural communities. Based on management practice theory, as well as guidance from the Chamber of Commerce and Industry (Kadin) and the Ministry of Cooperatives and MSMEs, the management practices for rural MSMEs include: 1) Efficient Inventory Management; 2) Production Process Improvement, particularly Production Efficiency; 3) Financial Management; 4) Human Resource Management; 5) Effective Marketing Strategies and the Use of Digital Marketing; and 6) Performance Evaluation and Control.